Correlation between electrical conductivity in saturated paste extracts and different diluted extracts (1/2.5, 1/5) of coarse-textured soils - Bakhti, Dahman; Oustani, Mabrouka; Halilat, Mohamed Taher; Zemour, Hafidh; Khadoumi, Amar; Belhouadjeb , Fathi Abdellatif (Future Science, 2024)
Soil salinity poses a significant challenge to agricultural productivity, necessitating precise measurement methods. Rather than relying on complex determinations like saturated paste extracts (ECe), a practical alternative involves assessing soil salinity through the Electrical Conductivity (EC) of soil-water extracts. This simplified yet reliable method is crucial for understanding the impact of soil salinity on agricultural yields. To improve accuracy in representing soluble salts relevant to plant growth, the conversion of EC from soil water extracts to ECe becomes pivotal.In an experimental study, a clear relationship was sought between the Electrical Conductivity (EC) of saturated paste extracts (ECe) and the ratios found in soil-water extracts (1/2.5 and 1/5). Fifty samples of coarse-textured soil were collected from the Djamâa palm grove in Sidi Yahia village, located in the Oued Righ region within the Djamaa Zone. The analysis of the collected data revealed compelling findings, indicating a robust and statistically significant correlation between values obtained from ECe and those derived from EC1/2.5 and EC1/5 (correlation coefficient of R = 0.93 and 0.91, at a significance level of P = 0.05). These results highlight the promising potential of accurately estimating ECe in coarse-textured soils by employing EC1/2.5 and EC1/5, paving the way for streamlining assessment methodologies for soil salinity. This study not only elucidates the correlation between conductivity measures but also proposes a practical means to estimate soil salinity more efficiently. The findings contribute to informed decision-making in agricultural practices within the Northern Sahara's Djamâa palm grove and similar regions, offering valuable insights for sustainable soil management.